Whistleblowing against doping in sport: A cross-national study on the effects of motivation and sportspersonship orientations on whistleblowing intentions. Issue 10 (19th May 2021) - Barkoukis, Vassilis; Bondarev, Dmitriy; Lazuras, Lambros; Shakverdieva, Sabina; Ourda, Despoina; Bochaver, Konstantin; Robson, Anna
ABSTRACT: Whistleblowing against anti-doping rule violations and related misconduct has been recognized as an important deterrent of doping behaviour in competitive sport. However, research on whistleblowing against doping is scarce and the available studies have focused on small samples using qualitative and inductive approaches. The present study used quantitative methods to assess, for the first time, the association between self-determined motivation, achievement goals, sportspersonship orientations and intentions to engage in whistleblowing against doping misconduct. A total of 992 competitive athletes from Greece ( n = 480) and Russia ( n = 512) completed structured measures of self-determination, achievement goals, sportspersonship orientation beliefs, and intentions to report doping misconduct. Latent profile analysis classified athletes into clusters consistent with the theoretical predictions. One-way analyses of variance further showed consistently across countries that autonomous motivated athletes reported higher intentions to whistleblow, and athletes with higher scores in achievement goals and sportspersonship orientations had significantly higher scores in whistleblowing intentions, compared to those with lower scores in these characteristics in both countries. This is the first study to demonstrate the association between motivational regulations, achievement goals, sportspersonship beliefs, and whistleblowing intentions. The theoretical and policy implications of our study are discussed.